Deans’ Roles in the Administration of Secondary Schools in an Education District in Trinidad and Tobago - Wihby, Rene Jerome; Joseph, Arthur (School of Education, UWI, 2018)
This paper, explores, through the lens of a Pastoral Care Model, deans’ actual roles in secondary schools, and the extent to which these roles were enacted. A qualitative multi-site case study, was employed to generate pertinent data from six secondary schools in a single education district. The sample comprised 6 principals, 12 deans and 67 teachers. Data were collected using semi-structured interviews to garner the perspectives of principals, teachers and deans. The findings suggest that most deans at the secondary schools, spent a disproportionate amount of their time monitoring student indiscipline. As a result, they were rarely engaged in the performance of their other prescribed roles.
Keywords: Educational Administration